Conducting health policy analysis in primary care research: turning clinical ideas into action. Issue 2 (22nd March 2019) - Engelman, Alina; Case, Ben; Meeks, Lisa; Fetters, Michael D
Abstract : Healthcare guidelines play a prominent role in the day-to-day practice of primary care providers, and health policy research leads to the formation of these guidelines. Health policy research is the multidisciplinary approach to public policy explaining the interaction between health institutions, special interests and theoretical constructs. In this article, we demonstrate how primary care providers can conduct high-impact health policy research using Eugene Bardach's eightfold policy analysis framework in a primary care context. In a medical case, a woman with a history of total hysterectomy had scheduled a visit for a Papanicolaou (Pap) smear screening test as part of a well-woman health check-up with a family medicine resident. Conflicting recommendations on Pap smear screening after total hysterectomy sparked an investigation using the US Preventive Services Task Force criteria for conducting a health policy analysis. We illustrate broadly how clinical care dilemmas can be examined by using Bardach's broadly applicable health policy framework in order to inform meaningful policy change. Bardach's framework includes (1) defining the problem, (2) assembling evidence, (3) constructing alternatives, (4) selecting criteria, (5) projecting outcomes, (6) confronting trade-offs, (7) decision-making and (8) sharing the results of the process. The policy analysis demonstrated insufficient evidence to recommend Pap test screening after hysterectomy and the findings contributed to national recommendations. By following Bardach's steps, primary care researchers have a feasible and powerful tool for conducting meaningful health policy research and analysis that can influence clinical practice.